تقنين عمر الزواج بين المانعين والمجيزين والتطبيقات القضائية - Jawad Faqi; Himdad Majeed; Saadi Hasan Baram (QALAAI ZANIST SCIENTIFIC JOURNAL, 2019)
The researchers presented the opinions of modern jurists who are divorced and rejecting the ruling on legalizing the age of marriage, And presented the most prominent evidence of the evidence of the Book and Sunnah We commented on the views of the two groups and identified the most likely views in the light of their evidence In harmony with the spirit of Sharia and the interest of the weak class, which can not defend its right and do not know its interest, And the necessity of the subject and its importance We referred to the legal articles and paragraphs of some foreign countries that have developed the law to codify the age of human to conduct a marriage contract, Including Arab and Islamic countries, And the international conventions on human rights and children, which considered the agreements to conduct marriage contract at a lower age than codified to make the marriage contract a crime committed against children,We also presented the legal articles and paragraphs of the Iraqi Personal Status Law and the Kurdistan Region on the legalization of the age of the person to conduct the marriage contract as an asset and base for conducting the marriage contract and any exceptions in this regard,We also presented the legal articles and paragraphs of the Iraqi Personal Status Law and the Kurdistan Region on the legalization of the age of the person to conduct the marriage contract as an asset and base for conducting the marriage contract and any exceptions in this regard